Analisis Respon K-Popers sebagai Korban Viktimisasi Narasi Derogatif di Media Sosial X - Syarifah Dwi Pratama (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The K-Pop phenomenon in Indonesia has experienced significant growth, with fans forming active digital communities on social media, particularly on X. However, this popularity is accompanied by the emergence of derogatory narratives that stigmatize K-Pop fans and idols through negative language. This study aims to identify patterns of derogatory narratives directed at K-Pop fans and idols on X and to analyze how fans respond to these narratives in digital interactions. This research employs a descriptive qualitative approach using digital methods, with social media data as the primary source. The findings show that derogatory narratives are constructed through repeated use of terms such as “stupid,” “idiot,” “sissy,” and “plastic,” which develop from individual labeling into broader generalizations. These narratives reinforce negative stereotypes and position fans as subordinate in digital spaces. Fans demonstrate diverse responses, both direct and indirect. Based on Stuart Hall’s reception theory, responses are predominantly oppositional and negotiated, indicating that fans tend to reject or reinterpret these narratives. Many also adopt a “lurker” role through coping strategies such as ignoring, blocking, or limiting interactions. These findings indicate that K-Pop fans are active agents who interpret and respond to stigma while maintaining their identity and community solidarity.